Perencanaan Instalasi Penangkal Petir Pada Bangunan Industri Furniture - Sukamdi; Sri Wahyuni Dali; Chandra Wiharya; Abdu Alimil Asror (UPT - P2M POLINEMA, 2022)
In planning external protection systems, the methods that are widely used are conventional and electrostatic lightning rod methods, therefore to study further, the results of observations that have been made to the industry there is still no lightning rod system so the author will try to plan and compare the plans of the two types of rods. lightning rods are Conventional ( Franklin ) and Electrostatic ( EF Lightning Protection System ) lightning rods in terms of protection, technical, economical, advantages and disadvantages. The research and observation methods were carried out in the furniture industry area of PT. Marufuji Kenzai Indonesia, with data collection techniques through direct observation, interviews, and literature studies, so that the building plan data (height, width and length of the building) are obtained and the 2020 thunder day data (IKL 238) then the data obtained is used to calculate the parameters in planning the installation of lightning rods according to the standards of SNI 03-7015-2004 and PUIPP. So that the results obtained for planning the conventional method ( Franklin ) with the placement of air terminations using the rolling ball method obtained 22 finials installed with buildings that can withstand currents of up to 160.1 kA and for the electrostatic method ( EF Lightning Protection System ) with 1 finial the building can withstand currents up to 25,891 kA, and if it exceeds this value a lightning rod will be caught.